Early Neurological Improvement Predicts Clinical Outcome After Thrombectomy for Distal Medium Vessel Occlusions - Wang, Maud; Farouki, Yousra; Hulscher, Franny; Mine, Benjamin; Bonnet, Thomas; Elens, Stephanie; Vazquez Suarez, Juan; Jodaitis, Lise; Ligot, Noémie; Naeije, Gilles; Lubicz, Boris; Guenego, Adrien (Frontiers in Neurology, 2022)
Background and Purpose Good clinical outcome predictors have been established in mechanical thrombectomy (MT) for acute ischemic stroke (AIS) caused by large vessel occlusion (LVO). An early neurological improvement (ENI), defined as a reduction of ≥8 on the National Institutes of Health Stroke Scale (NIHSS), compared with the baseline score or an NIHSS of 0 or 1 at 24 h after MT, is a strong predictor of favorable outcome. We aimed to study the impact of ENI after MT for distal medium vessel occlusions (DMVO). Methods We retrospectively analyzed the data of consecutive patients who underwent MT for a primary DMVO in one large academic center. We compared clinical outcomes between patients with DMVO stratified by ENI. Multivariate analyses were performed to determine the impact of ENI on good 90-day outcome (modified Rankin scale of 0–2) and identify factors contributing to ENI. Results Between January 2018 and January 2021, 61 patients underwent an MT for an AIS with a primary DMVO. An ENI was seen in 24 (39%) patients (ENI+). Outcomes were significantly better in ENI+ patients, with 83% achieving a good outcome at 3 months vs. 43% for patients without ENI (ENI–; p = 0.019). ENI was an independent predictive factor of good clinical outcome even after adjusting for potential confounding factors [odds ratio 12.49 (1.49–105.01), p = 0.020]. The use of intravenous tissue plasminogen activator [IVtPA; Odds-ratio 6.59 (1.82–23.89), p = 0.004] was a positive predictor of ENI. Conclusion ENI at day 1 following MT for DMVO stroke is a strong independent predictor of good to excellent 3-month clinical outcome.